Pemahaman Konsumen Terhadap Brand Awernes Produk Skincare Azarine - Ihsan Firmansyah; Resya Siti Kulsum; Agil Permana; Helin Garlinia Yudawisastra (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This study aims to explore consumer understanding of brand awareness toward Azarine skincare products. A qualitative descriptive approach was employed in this research. The data were obtained from secondary sources through non-participant observation of Azarine’s official social media content and documentation in the form of consumer reviews and testimonials available on e-commerce platforms. Data analysis was conducted through data reduction, thematic categorization, and conclusion drawing. The findings indicate that consumer understanding of Azarine’s brand awareness is formed through intensive digital exposure and consistent brand communication. Consumers do not merely recognize Azarine as a local skincare brand but also understand its brand identity as affordable, easily accessible, and suitable for various skin needs. Furthermore, Azarine’s brand awareness is perceived as a sense of familiarity and initial trust toward the products. This study contributes to the literature on brand awareness by providing a qualitative perspective, particularly within the context of Indonesia’s local skincare industry.